Personality, Defense Mechanisms and Psychological Distress in Women with Breast Cancer (Journal of Pharmaceutical Negative Results, 2023)
Background Many  studies have shown that many personality traits are associated with breast cancer (BC), worsening both the quality of life and psychological distress of patients. These increased levels of distress increase the risk of depression and anxiety with subsequent adverse effect on compliance to cancer treatment. Despite the high comorbidity of psychopathological disorders in this disease and their association with defense styles, few studies have examined the defense mechanisms used by BC patients. The main aim of our study was to investigate personality disorders and defense mechanisms in BC patients. Objective The aim of this study was to detect psychiatric comorbidity and impact of defense style, personality variables in patients with breast cancer and study their relations with tumor grading and histopathological characteristics. Patients and Methods In this cross-sectional study. About 150 patients with breast cancer were  evaluated for having breast cancer according to laboratory, radiological and pathological  investigations. Participants were females aged 18 years or older. Patients with history of another cancer, comorbid serious medical condition, in their investigation phase of cancer diagnosis or those who refused to participate in the study were excluded. The tools applied to participants were the Symptom Checklist 90 Revised, Defense style Questionnaire-40 and Structured Clinical Interview for DSM- IV Axis II (SCID-II) . Results One hundred thirteen patients (75.3%) had psychiatric comorbidity; somatization was the most common psychiatric comorbidity (58.7%) followed by depression (40.7%). Patients with and without comorbid psychiatric illness used mature defense mechanisms than neurotic and immature defenses. Personality variables which is related to pattern of use of  defense mechanisms, in order of   the mean mature defenses came first followed by neurotic followed by immature defense mechanisms and we found that (22%) of patients had criteria of obsessive – compulsive personality, (18.7%) had borderline criteria, (16.7%) had dependent criteria Conclusions Psychiatric comorbidity are common in patients with breast cancer. Personality characteristics and  defense style used by breast cancer patients could shape the presenting psychiatric disorder